A Politics of Working-Class Culture and the Culture of Working-Class Politics: The Aesthetics and Activism of Amber Film and Photography Collective and the Berwick Street Film Collective - Jessica Williams Boyall (Open Library of Humanities)
This paper examines how Amber Film and Photography Collective’s working-class affiliations and Berwick Street Film Collective’s middle-class makeup shaped their divergent approaches to depicting ‘working-class issues’ by drawing on the films of both collectives, alongside archival materials and oral testimonies. By engaging in a comparative reading, I highlight the breadth of Amber’s oeuvre, tracing the development of their filmmaking strategies—which included agitprop, the fusion of factual and fictional formal elements and transnational collaboration with the German Democratic Republic’s film production company, Deutsche Film-Aktiengesellschaft (DEFA)—to demonstrate that, contrary to criticisms levelled by contemporary theorists clustered around Screen magazine and the British Film Institute, Amber transcended the constraints of Documentary Realism by incorporating radical avant-garde aesthetics into their oppositional practice. Concomitantly, Amber’s radical filmmaking is positioned as relative to its members’ working-class solidarities, with their concern for championing working-class cultures contrasted with Berwick Street’s broader political agendas. Through foregrounding this politics/culture dialectic, the practical repercussions of Berwick Street’s middle-class representation of ‘working-class interests’ are investigated while the theoretical criteria by which avant-garde depictions of ‘working-class issues’ are evaluated are themselves assessed.